2022
DOI: 10.3389/fpls.2022.1010569
|View full text |Cite
|
Sign up to set email alerts
|

On the nature of the plant ER exit sites

Abstract: In plants, the endoplasmic reticulum (ER) and Golgi bodies are not only in close proximity, but are also physically linked. This unique organization raises questions about the nature of the transport vectors carrying cargo between the two organelles. Same as in metazoan and yeast cells, it was suggested that cargo is transported from the ER to Golgi cisternae via COPII-coated vesicles produced at ribosome-free ER exit sites (ERES). Recent developments in mammalian cell research suggest, though, that COPII help… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…By expressing CrSar1‐YFP in the Chlamydomonas expression strain UVM11 (Barahimipour et al, 2016 ; Neupert et al, 2009 ), we observed a cytosolic accumulation pattern of the YFP signal, with punctate structures distributed in the cytosol (Figure 2a ). In Arabidopsis and tobacco, the Sar1‐containing punctate structures are closely associated with the ER, representing putative COPII assembly and ER exit sites (ERES) (McGinness et al, 2022 ; Takagi et al, 2020 ; Zeng et al, 2015 ). To further examine the CrSar1‐containing punctate structures in the alga, we next co‐expressed CrSar1‐YFP with the ER marker mCerulean‐HDEL (Rasala et al, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…By expressing CrSar1‐YFP in the Chlamydomonas expression strain UVM11 (Barahimipour et al, 2016 ; Neupert et al, 2009 ), we observed a cytosolic accumulation pattern of the YFP signal, with punctate structures distributed in the cytosol (Figure 2a ). In Arabidopsis and tobacco, the Sar1‐containing punctate structures are closely associated with the ER, representing putative COPII assembly and ER exit sites (ERES) (McGinness et al, 2022 ; Takagi et al, 2020 ; Zeng et al, 2015 ). To further examine the CrSar1‐containing punctate structures in the alga, we next co‐expressed CrSar1‐YFP with the ER marker mCerulean‐HDEL (Rasala et al, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…Why was this cis -Golgi network never observed before in plant cells? Actually, membrane tubules were suggested to exist between the ER and the plant Golgi for a long time 12,13,45 . However, previous immuno-EM experiments using cis -Golgi markers were all focused on the Golgi stack and, consistently with our results, all show a pearled membrane structure at the cis -side of the stack 7,40,46,47 .…”
Section: Discussionmentioning
confidence: 99%
“…In plant cells, due to the close proximity of the Golgi and ERES, it has been suggested that no equivalent of the ERGIC exists 6,12 . However, it has been described that some part of the ER, or some ER-derived protrusions, can from contacts with the Golgi apparatus 7,[13][14][15] . In addition, it has been observed that inducing Golgi movement by trapping the Golgi with optical tweezers results in the dynamic remodeling of the ER network, thereby suggesting that the ER and the Golgi are in physical contact 16 .…”
Section: Mainmentioning
confidence: 99%
“…VAP27 is likely to participate in most of these connections according to the literature in mammalian systems and plants. (b–d) A few examples of ER–organelle interactions at the light microscopy level in plants, such as ER (GFP‐HDEL) and Golgi bodies (ST‐RFP; Bar, 1 μm; McGinness et al ., 2022); ER (GFP‐HDEL) and mitochondria (Mito‐mCherry; Bar, 2 μm; Li et al ., 2022); ER (RFP‐HDEL) and autophagosomes (NAP1‐GFP; Bar, 2 μm; Wang et al ., 2016a). All images were taken from tobacco leaf epidermal cells.…”
Section: Introductionmentioning
confidence: 99%